The effect of smokeless tobacco uses and exposure to cigarette promotions on smoking intention among youths in Ghana (2018)
Although controversial, smokeless tobacco use has been implicated as a gateway for smoking. Furthermore, most existing studies did not explore the potential of smokeless tobacco use as a proxy for receptivity to cigarette advertisement rather than an independent predictor of smoking. This study sought to determine the independent effect of smokeless tobacco use, as well as exposure and receptivity to cigarette advertisements on smoking intention among Ghanaian youths. Secondary data obtained from Ghanaian adolescents who participated in the Global Youth Tobacco Surveys conducted during 2006 and 2009 were analyzed using Stata version 13. Data analysis was restricted to current non-smokers and included descriptive and inferential statistics. Intention to smoke for both survey years was associated with: smokeless tobacco use, (OR = 3.74: 95% CI = 2.63–5.32), limited exposure to anti-smoking media messages, (OR = 1.70: 95% CI = 1.09–2.65), being offered cigarettes by tobacco representatives (OR = 2.19: 95% CI = 1.42–3.37) and reporting having both parents (OR = 4.42; 95% CI = 1.84–10.59) or a lot of friends (OR = 3.03: 95% CI = 1.87–4.89) who were smokers. Smokeless tobacco use and exposure to tobacco industry’s promotional activities independently influenced smoking intentions among youths in Ghana. Therefore, complete ban of all forms of tobacco products promotional activities needs to be intensified.